Nursi’s Role to Spread Harmony and Peace in the Perspective of Rasail-E-Nur - Mohd Saqib; Sumaira Mohammad Ajmal (LECTURES: Journal of Islamic and Education Studies, 2026)
Bediuzzaman Said Nursi (1877–1960), a prominent twentieth-century Islamic scholar, dedicated his life to conveying the Qur'anic message through his writings and teachings, particularly the Risale-i Nur. The objective of this study is to examine Nursi's role in promoting social harmony from the perspective of the Risale-i Nur by analyzing his intellectual mission, the reformative significance of his writings, and their contribution to peaceful coexistence. The methodology adopts a qualitative, descriptive, and analytical approach based on textual analysis of the Risale-i Nur and a critical review of relevant scholarly literature. The findings indicate that Nursi's teachings foster faith, moral consciousness, compassion, tolerance, justice, and freedom of belief, thereby strengthening social cohesion among Muslims and non-Muslims. His response to irreligion and moral decline is grounded not in conflict or coercion but in rational persuasion, ethical education, and spiritual transformation inspired by the Qur'an. The study concludes that Nursi's faith-based, wisdom-oriented, and non-violent approach provides a practical framework for building resilient, morally grounded, and harmonious societies. His intellectual legacy remains highly relevant for addressing contemporary social challenges and promoting sustainable peace, spiritual renewal, and intercommunal harmony in pluralistic societies.